Psychological Consequences of inaccessibility of the redesigned Naira notes in Abakaliki Metropolis - Eze Ogbonnia; Chisom Cherish Oselebe (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
This study is informed by the several lamentations of Nigerians as the redesigned naira notes are not available neither are the old notes useable. The study is a qualitative inquiry into the difficulties and psychological implications of the currency dilemma experienced in Abakaliki Metropolis, Ebonyi State Nigeria. 30 respondents were interviewed across 6 banks and Automatic Teller Machines (ATM) outlets in Abakaliki metropolis. Participants were selected using convenience sampling technique. Interview methods of data collection were adopted for collecting information regarding Nigerian citizens’ experiences of the currency crisis orchestrated by the introduction of the new naira notes in the country. The study was designed as a phenomenological research and data was analysed through interpretive phenomenological analysis (IPA). Findings reveal that the challenges of accessing the new naira notes affected the psychological wellbeing of the participants. Their experiences of the currency crisis were overwhelming leading to conditions of trauma, helplessness, frustration, anxiety of survival, uncertainty, powerlessness and hopelessness. All of these conditions affected their psychological wellbeing and mental life. Results further shows that participants got relief from telling the stories of their experiences of the dilemma which served as a coping mechanism for them. It was recommended that the Federal government of Nigerian and the Central bank of Nigeria should intensify efforts to solve the currency problems and ameliorate the conditions of living of the teeming Nigerian population. Mental health workers are also encouraged develop programmes and activities to help Nigerians negotiate the current currency situation affecting the mental life of majority of the people living in the country.